Law Enforcement On Agents Assignment/Transfer Tube Gas Subsidies To Non LPG Subsidies - Fakhrul Wildan; Gunarto Gunarto (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
The problems of this study are: law enforcement against businesses diversion / transfer of LPG gas cylinders subsidized to non-subsidized according to the Law of Legal Metrology and Consumer Protection which handled by Special Criminal Investigation Directorate Central Java Police and barriers faced by the Special Criminal Investigation Directorate Central Java Police to businesses diversion / transfer of LPG gas cylinders subsidized to non-subsidized and solutions.The method used by researchers is normative juridical law approach and specification in this study were included descriptive analysis. Eventhough sources and types of data in this study are primary data obtained from field studies with interview Central Java Police investigators Ditreskrimsus, and secondary data obtained from the study of literature relating to the theory of the legal system.Based on the results of research that law enforcement against criminal cases the transfer of gas in gas cylinders subsidized gas cylinder non-subsidized conducted by the Police Directorate of Special Criminal Investigation Police Central Java starting from reports from the public or the findings of its own from the police, subsequently reduced to a letter of assignment to conduct an investigation, and then do a degree case to begin their investigation. Constraints: the views of the legal system, structure, substance and legal culture. The solution is to provide the sanction of the crime of diversion of gas, so that the person must have a deterrent effect and does not make the crime of diversion of gas from happening again. In the event of transfer of LPG cylinder which disturb public, then the aggrieved community can make a complaint to the authorities.Keywords : Law enforcement; business communities; Legal Metrology; Consumer Protection